One breath away - Gudenkauf, Heather (Harlequin MIRA Books, 2012)
In the midst of a sudden spring snowstorm, an unknown man armed with a gun walks into an elementary school classroom. Outside the school, the town of Broken Branch watches and waits. Officer Meg Barrett holds the responsibility for the town's children in her hands. Will Thwaite, reluctantly entrusted with the care of his two grandchildren by the daughter who left home years earlier, stands by helplessly and wonders if he has failed his child again. Trapped in her classroom, Evelyn Oliver watches for an opportunity to rescue the children in her care. And thirteen-year-old Augie Baker, already struggling with the aftermath of a terrible accident that has has brought her to Broken Branch, will risk her own safety to protect her little brother. As tension mounts with each passing minute, the hidden fears and grudges of the small town are revealed as the people of Broken Branch race to uncover the identity of the stranger who holds their children hostage.